Gut Microbiota-Derived PGF2α Fights against Radiation-Induced Lung Toxicity through the MAPK/NF-κB Pathway - Zhi-Yuan Chen; Hui-Wen Xiao; Jia-Li Dong; Yuan Li; Bin Wang; Sai-Jun Fan; Ming Cui (MDPI AG, 2021)
Radiation pneumonia is a common and intractable side effect associated with radiotherapy for chest cancer and involves oxidative stress damage and inflammation, prematurely halting the remedy and reducing the life quality of patients. However, the therapeutic options for the complication have yielded disappointing results in clinical application. Here, we report an effective avenue for fighting against radiation pneumonia. Faecal microbiota transplantation (FMT) reduced radiation pneumonia, scavenged oxidative stress and improved lung function in mouse models. Local chest irradiation shifted the gut bacterial taxonomic proportions, which were preserved by FMT. The level of gut microbiota-derived PGF2α decreased following irradiation but increased after FMT. Experimental mice with PGF2α replenishment, via an oral route, exhibited accumulated PGF2α in faecal pellets, peripheral blood and lung tissues, resulting in the attenuation of inflammatory status of the lung and amelioration of lung respiratory function following local chest irradiation. PGF2α activated the FP/MAPK/NF-κB axis to promote cell proliferation and inhibit apoptosis with radiation challenge; silencing MAPK attenuated the protective effect of PGF2α on radiation-challenged lung cells. Together, our findings pave the way for the clinical treatment of radiotherapy-associated complications and underpin PGF2α as a gut microbiota-produced metabolite.